A mixed-methods process evaluation of the feasibility and acceptability of involving community and peer role models within a physical activity intervention for primary-school-aged girls (the CHARMING study) - Kelly Morgan; Jordan Van Godwin; Rebecca Cannings-John; Britt Hallingberg; Graham Moore; Bethan Pell; Holly Whiteley; Jemma Hawkins (BMC, 2023)
Abstract Background Role models have been identified as a potential means to tackle the persisting low levels of physical activity among young girls. The aim of this research was to explore the involvement of community- and peer role models within the CHARMING (CHoosing Active Role Models to INspire Girls) intervention, an intervention which aims to increase and sustain physical activity among 9-10-year-old girls. The research questions were, is it feasible and acceptable to recruit role models? and what are the perceived barriers and facilitators to the inclusion of peer role models within the intervention? Methods A mixed methods process evaluation was embedded within a larger feasibility study, involving three secondary schools and four adjoining primary schools in South Wales, United Kingdom. One-to-one interviews were conducted with teachers (N = 10) across the seven schools and community role models (N = 10). Focus groups were conducted with 18 peer role models (older girls from adjoining secondary schools) and 18 girls aged 9-10-years who had participated in the intervention. Primary school teachers kept observation logs of each intervention session. A researcher completed observation logs of two random sessions per school. Qualitative data were analysed using thematic analysis with a combined deductive and inductive coding approach. Observation data were analysed using descriptive statistics. Data were triangulated and comparative analyses conducted across schools. Results Twenty-three peer role models (aged 12-16-years) and 16 community role models participated in intervention delivery. Overall, the inclusion of both types of role models was shown as acceptable and feasible within the CHARMING intervention. Observation data highlighted key areas (i.e., intervention components delivered inconsistently) for further qualitative exploration. Six themes were identified during analyses; reach and access, communication, logistics, existing systems, interpersonal relationships, and perceived impacts. Themes were intertwined across the barriers and facilitators of recruitment and implementation. Areas for future improvement were highlighted. Conclusions Findings can be used to optimise the CHARMING intervention and inform wider interventions or policies employing several role models across settings to promote physical activity among children.